On the Issue of the Possibility for a Court to Use Expert Techniques in Determining the Proportions of Compensation for Property Damage Caused by a Traffic Accident - D. V. Sedov; A. I. Sirokhin (Теория и практика судебной экспертизы, 2019)
The study of the features of compensation for harm caused by a high-risk object is important both from theoretical and practical points of view. The article attempts to justify the possibility for a court to use expert techniques in determining the proportions of compensation for property damage caused by a traffic accident resulting from inadequacy of road conditions to safety requirements. The subjective basis for imposing liability on a driver for the damage caused by the accident is the high-risk object owner’s conscious choice to carry out activities entailing an accidental harmful result. When considering the cases of this category, the court may face the problem of determining the proportions of compensation for the damage that has arisen from the inadequacy of the driving to the requirements of traffic regulations and from negligence in the performance of duties by the road services. In this case, it is proposed to determine the proportions of damages from the standpoint of rationale for the extent of the driver’s technical ability to prevent the accident.